Advancement in modeling of Alzheimer’s disease: a comprehensive review of preclinical screening platforms - Adak, Souvik; Singh, Shivam; Jain, Ridhi; Tiwari, Abhilasha; Singh, Binny; Kumar, Sumit; Dadhwal, Ayushi; Chakroborty, Avishek; Sharma, Ashish Kumar; Singh, Ravindra Pal; Sharma, Rajesh Kumar (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a chronic and progressive neurodegenerative condition that worsens with time and causes memory loss and cognitive impairment. For prompt intervention and management of AD, early detection is essential. Screening models play a crucial role in identifying individuals at risk of developing AD before the onset of noticeable clinical symptoms. This review summarizes a wide range of in vitro and in vivo screening models currently utilized in AD research, highlighting their advantages and limitations. In vitro systems-such as cell lines and primary neuronal cultures-provide controlled settings to investigate cellular mechanisms and drug efficacy. In contrast, in vivo models, including transgenic rodents and other animals, better replicate the complex biological features of AD. Each model type comes with distinct benefits and limitations concerning clinical relevance, cost-effectiveness, and ethical challenges. By evaluating the utility and constrains of these models, this article seeks to assist researchers in choosing suitable platforms for preclinical investigations and support the advancement of improved diagnostic tools and therapeutic strategies for AD.